The courses of purposes and their impact on Islamic legislation (Journal of the College of Basic Education, 2022)
This head examines the origin of Islamic legislation, namely the purposes of sharia in terms of the courses by which these purposes are proven and its impact on the legislation of the provisions, to identify their ills as much as possible, to identify the methods of scholars in those courses and then to identify the investigation of their shortcomings